Anti-progressive collapse performance analysis of composite frame with openings on beam web. (October 2020) - Meng, Bao; Zhong, Weihui; Hao, Jiping; Tan, Zheng; Wang, Limin
Abstract: Few studies have been conducted on the anti-progressive collapse performance of composite frames with openings on the beam web, which are commonly employed in the construction of steel-framed buildings. In this study, two one-third scale composite substructures with web solid beams (WUF) and web opening beams (WUFO) were investigated by conducting quasi-static tests. The test results indicated that the damage mode of the specimens was due to the failure of the tension beam flange connected to the column, accompanied by the tearing and breaking of the profile decking and reinforcement bars. The stress process of the specimens mainly comprises three stages, namely, the elastic stage, compressive arching stage, and flexure-catenary mixed stage. In the compressive arching stage, the bearing capacity of WUFO was found to be 11.3% lower than that of WUF. In the flexure-catenary mixed stage, the maximum bearing capacity and corresponding displacement of WUFO increased by 48.1% and 32.4% when compared with that of WUF. The appropriate openings on the beam web were conducive to the development of the beam-end rotation and the axial forces in the composite beams. Based on the refined numerical models, which were experimentally verified, the influence of the opening diameter, end distance, and opening spacing on the anti-collapse performance of the composite substructure was discussed; and suitable ranges of these parameters were suggested. Graphical abstract: The failure mode, deformation capacity, internal forces development, and resistance mechanism of the composite substructures with web solid beams (WUF) and web opening beams (WUFO) were investigated and analysed by conducting quasi-static tests and using full-scale numerical models. The appropriate openings on the beam web were conducive to the development of the beam-end rotation and the axial forces in the composite beams. Unlabelled Image Highlights: Anti-collapse performance of composite substructure with web opening beams was evaluated. Specimens were damaged due to failure of tension flange of beam connected to column. Appropriate openings on beam web were conducive to the development of the beam-end rotation and the axial forces in the composite beams. Suitable ranges of opening parameters were suggested.